2019
DOI: 10.1084/jem.20182316
|View full text |Cite
|
Sign up to set email alerts
|

The epigenetic regulator ATF7ip inhibits Il2 expression, regulating Th17 responses

Abstract: T helper 17 cells (Th17) are critical for fighting infections at mucosal surfaces; however, they have also been found to contribute to the pathogenesis of multiple autoimmune diseases and have been targeted therapeutically. Due to the role of Th17 cells in autoimmune pathogenesis, it is important to understand the factors that control Th17 development. Here we identify the activating transcription factor 7 interacting protein (ATF7ip) as a critical regulator of Th17 differentiation. Mice with T cell–specific d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Although further analysis, including corepressor recruitment, determination of histone marks, or even HiC approaches, will be necessary to fully unravel the detailed mode of interaction of NR2F6 within the Il21 promoter, as well as intergenic Il21 - Il 2 region, our data provide strong evidence for a critical functional role of NR2F6 in the Tfh cell effector compartment. DNA methylation and histone modification have not yet been investigated within this project, but their importance for the regulation of the Il2 - Il21 region have been shown (Sin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Although further analysis, including corepressor recruitment, determination of histone marks, or even HiC approaches, will be necessary to fully unravel the detailed mode of interaction of NR2F6 within the Il21 promoter, as well as intergenic Il21 - Il 2 region, our data provide strong evidence for a critical functional role of NR2F6 in the Tfh cell effector compartment. DNA methylation and histone modification have not yet been investigated within this project, but their importance for the regulation of the Il2 - Il21 region have been shown (Sin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, STAT3 binding to the IL-17 promoter is associated with an elevation of the H3K4me3 at the IL-17 loci, which is therefore necessary for the expression of Th17-specific cytokines IL-17 and IL-21 41 . In addition, ATF7ip, an epigenetic regulator for H3K9me3 expression, as a repressor of IL2 gene expression through H3K9me3 deposition in the IL2-IL21 intergenic region, plays an important role in Th17 differentiation 42 .…”
Section: Epigenetics Of Immune Cell Developmentmentioning
confidence: 99%
“…These data suggest that BET plays an important role in CD4 + Th-17 cell generation and persistence. Another report identified ATF7ip (activating transcription factor 7 interacting protein, also known as MCAF1 or mAM), an epigenetic regulator responsible for repressive H3K9me3 marks via its histone methyltransferase-binding partners SETDB1/ESET [ 47 ], as a crucial regulator of Th-17 differentiation [ 48 ]. Depletion of Atf7ip ( Cd4-Cre ) resulted in impaired Th-17 differentiation and enhanced production of IL-2 in response to T cell receptor (TCR) stimulation [ 48 ].…”
Section: Epigenetic Changes During T Cell Differentiationmentioning
confidence: 99%
“…Another report identified ATF7ip (activating transcription factor 7 interacting protein, also known as MCAF1 or mAM), an epigenetic regulator responsible for repressive H3K9me3 marks via its histone methyltransferase-binding partners SETDB1/ESET [ 47 ], as a crucial regulator of Th-17 differentiation [ 48 ]. Depletion of Atf7ip ( Cd4-Cre ) resulted in impaired Th-17 differentiation and enhanced production of IL-2 in response to T cell receptor (TCR) stimulation [ 48 ]. They further showed that ATF7ip acts as an IL-2 inhibitor via suppression of Il2 gene expression through H3K9me3 deposition in the Il2-Il21 intergenic region [ 48 ].…”
Section: Epigenetic Changes During T Cell Differentiationmentioning
confidence: 99%
See 1 more Smart Citation